2018
DOI: 10.4102/aveh.v77i1.400
|View full text |Cite
|
Sign up to set email alerts
|

Stereoacuity and refractive, accommodative and vergence anomalies of South African school children, aged 13–18 years

Abstract: Aim:The aim of this study was to explore possible associations between stereoacuity and refractive, accommodative and vergence anomalies. Methods:The study design was cross-sectional and comprised data from 1056 high school children aged between 13 and 18 years; mean age and standard deviation were 15.89 ± 1.58 years. Using a multi-stage random cluster sampling, participants were selected from 13 high schools out of a sample frame of 60 schools in the municipality concerned. In the final sample, 403 (38%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…Poor amplitudes of accommodation could have contributed to their study findings because accommodation dysfunctions were also found to impact on stereoacuities. 19,20 Even though in this study significant associations (p = 0.00) between induced blur monocularly and binocularly using the 2 D and 3 D lenses were found, their correlation was found to be weak with r = 0.45 and 0.22, respectively. Contrary to the findings of the study conducted by Yang et al, 21 which found a significant correlation between different groups of spherical errors and stereoacuity measured and thus concluded that high hyperopia (> 3 D) severely reduced stereoacuity.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Poor amplitudes of accommodation could have contributed to their study findings because accommodation dysfunctions were also found to impact on stereoacuities. 19,20 Even though in this study significant associations (p = 0.00) between induced blur monocularly and binocularly using the 2 D and 3 D lenses were found, their correlation was found to be weak with r = 0.45 and 0.22, respectively. Contrary to the findings of the study conducted by Yang et al, 21 which found a significant correlation between different groups of spherical errors and stereoacuity measured and thus concluded that high hyperopia (> 3 D) severely reduced stereoacuity.…”
Section: Discussioncontrasting
confidence: 69%
“…However, there are still ongoing debates related to reduced vision monocularly or binocularly and their severity on stereoacuity. 17 Wajuihian and Hasraj, 18,19 in their study investigated the relationship between stereoacuity, refractive status, accommodative and vergence anomalies of South African school children with a mean age 15.89 ± 1.58 years and concluded that accommodative and convergence dysfunctions affected stereoacuity. Furthermore, participants with anisometropia were found to have significantly reduced mean stereoacuities compared to those with emmetropia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors that cause inappropriate development of stereopsis are many; one notable cause being uncorrected refractive errors. 8,11,12 All types of refractive errors adversely affect stereopsis by inducing visual blur, resulting in decreased binocular function with low sensory fusion. 8,13 In this study, subnormal stereopsis was found more in simple myopia, followed by compound myopic astigmatism and amblyopia.…”
Section: Discussionmentioning
confidence: 99%
“…Convergence insu ciency was more likely to occur in patients with a lower degree of myopia, while divergence insu ciency was more likely to occur in patients with a higher degree of myopia [7]. Another clinical study revealed that high school children (aged between 13 and 18 years) with refractive errors, accommodative or vergence anomalies were more likely to have reduced mean stereoacuity than cases without such anomalies [8]. Kirwan and O'keefe [9] believed that stereopsis was related to anisometropia and that every 0.25 D difference of binocular refraction can cause a 0.5% difference in the retinal image.…”
Section: Introductionmentioning
confidence: 99%